The role of social media in institutional communication. Case study: The Facebook page of Constanta City Hall - Rus, Mihaela; Tasente, Tanase; Ilie, Bianca-Irina; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2021)
In this research paper I chose to make a detailed analysis of the role of Social Media in institutional communication, focusing in the case study on observing the Facebook page of Constanta City Hall, this page being an important means of communication with citizens of the public institution concerned. In other words, I chose this topic because I consider extremely important the public relations department within a public institution, such as Constanta City Hall, after completing undergraduate studies applying for a position in this field being a main option for me. The main objective of the paper was to analyze institutional communication in its various forms, but especially the external communication of public institutions, the way of transmitting information from them to citizens being a very important aspect in terms of proper functioning of public administration.